2013
DOI: 10.1080/01635581.2013.824991
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Xenobiotic Metabolizing Genes, Intakes of Heterocyclic Amines and Red Meat, and Postmenopausal Breast Cancer

Abstract: Heterocyclic amines (HCAs) are mutagenic compounds generated when meats are cooked at high temperature and for long duration. The findings from previous studies on the relation between HCAs and breast cancer are inconsistent, possibly due to genetic variations in the enzymes metabolizing HCAs. To evaluate whether the associations of intakes of estimated HCAs, meat-derived mutagenicity (MDM), and red meat with risk of postmenopausal breast cancer were modified by N-acetyltransferase 2 (NAT2) acetylator genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Similar findings have been reported for the Nashville Breast Health Study [81] and the NIH-AARP Diet and Health Study among both, pre- and postmenopausal women [82]. Red and processed meats consist of heterocyclic amines, n -nitroso compounds, and polycyclic aromatic hydrocarbons, all of which are potential human carcinogens [17, 83]. Meat also contains animal fats and saturated fats, which are associated with the increased risk of breast cancer, in particular of the ER+/ER− and HER2-subtypes [8486].…”
Section: Dietary Factors and Nutrition In Breast Cancer Risksupporting
confidence: 74%
“…Similar findings have been reported for the Nashville Breast Health Study [81] and the NIH-AARP Diet and Health Study among both, pre- and postmenopausal women [82]. Red and processed meats consist of heterocyclic amines, n -nitroso compounds, and polycyclic aromatic hydrocarbons, all of which are potential human carcinogens [17, 83]. Meat also contains animal fats and saturated fats, which are associated with the increased risk of breast cancer, in particular of the ER+/ER− and HER2-subtypes [8486].…”
Section: Dietary Factors and Nutrition In Breast Cancer Risksupporting
confidence: 74%
“…In addition, three nested case–control studies and two clinical trial studies (not testing either red meat or processed meat) met inclusion criteria for red/processed meat. Furthermore, two studies met inclusion criteria regarding the interaction between red meat consumption and NAT2 polymorphisms on risk of breast cancer (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these differences in enzyme activity may modify the carcinogenic effect of red meat. However, regarding the interaction between meat consumption and NAT2 polymorphisms on risk of breast cancer, evidence in epidemiological studies is sparse and conflicting, and it has not been evaluated in published meta‐analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence for a causal relationship between processed meat and breast cancer is limited and mainly observed in case-control studies where a genetic polymorphism in N-acetyltransferase 2 has been investigated in relation to the presence of HCA in foods (e.g., [ 209 ]). However, recent evidence does not suggest that polymorphisms in genes that metabolize HCAs ( N -acetyltransferase 2 and CYP 1A12) modify colon or breast cancer risk [ 210 , 211 ]. In the National Institutes of Health (NIH)—AARP Diet and Health prospective study, there is suggestive evidence implicating HCAs found in red meat cooked at high temperatures in gastric cardia and non-cardia adenocarcinomas although the association never reached statistical significance [ 212 ].…”
Section: Meatmentioning
confidence: 99%